120 Evaluation of ovulation synchronization protocols and alternative pregnancy diagnosis tools in lactating dairy cows. (7th December 2018) - Shahzad, A; Abbas, A; Nak, D; Nak, Y; Khan, I; Mughal, Z
Abstract: Our objectives were to appraise three ovulation synchronization protocols and Pregnancy diagnosis(PD) methods in lactating dairy cows. Cows (n=184;4.2 ± 1.2 lactations and average daily milk yield>28 kg with 3X milkings) were randomly assigned to 1 of 3 timed artificial insemination(TAI) protocols: 1)Ovsynch protocol (n=66), GnRH-PGF2α -GnRH; 2)G7G-Ovsynch (n=63) protocol, PGF2α, GnRH 2 days later followed by Ovsynch; 3)PG7G-Ovsynch(n=55) protocol, PGF2α 14d before the start of G7G-Ovsynch protocol.Pregnancy rate(PR) was determined on d30, d60 and d90 post TAI using ultrasonography(US), P4(RIA), milk and Plasma PAGs(ELISA). The PR was compared using chi-square. Milk, plasma PAGs and plasma P4 profiles were analyzed using REG procedures of SAS(P<0.05). Ovarian status was monitored prior to enrollment and at final GnRH of individual protocol. Ovulatory follicle diameter(OFD) was 15.32 ± 0.18(Ovsynch), 15.06 ± 0.16(G7G-Ovsynch) and 15.14 ± 0.13(PG7G-Ovsynch) respectively. The PR on d30 was 44%(29/66), 51%(32/63) and 56%(3/55) in Ovsynch, G7G-Ovsynch and PG7G-Ovsynch( P =0.39) protocols respectively. On d60 post TAI, PR was 39%(26/66), 48%(30/63) and 53%(29/55) in all three groups( P =0.33). Similarly, PR was 38%(25/66), 48%(30/63) and 51%(28/55) with overall pregnancy loss of 14%, 6%(2/32) and 10%(3/31) in Ovsynch, G7G-Ovsynch and PG7G-Ovsynch groups respectively on d90 post TAI. Plasma P4 profile (ng/ml; Mean±SEM) was 7.40 ± 0.53, 7.75 ± 0.64 and 7.13 ± 0.42 on d30, d60 and d90 post TAI respectively. Optical density(OD) of milk PAGs was 1.06 ± 0.12, 0.48±.04 and 0.96 ± 0.11 on day 30, 60 and 90 post TAI respectively. Likewise, plasma OD was 1.82 ± 0.10, 0.87 ± 0.05 and 1.66 ± 0.12 on d30, d60 and d90 post TAI. Sensitivity(Se), Specificity(Sp), positive predictive value(PPV) and negative predictive value(NPV) of milk and plasma PAGs based test in present study was 98%(95% CI:91–100), 100%(95% CI:94–100), 100% and 98%(95% CI:89–99) respectively in comparison with US on the PD basis. Similarly, Se, Sp, PPV and NPV of plasma P4 test in present study was 100%. In conclusion, introduction of presynch based protocols have been resulted in improved, although non-significant, PR in lactating dairy cows and PAGs are other apposite PD tools.